A multi-locus genome-wide association study reveals the genetics underlying muscadine antioxidant in berry skin - Park, Minkyu; Darwish, Ahmed G.; Elhag, Rashid I.; Tsolova, Violeta; Soliman, Karam F. A.; El-Sharkawy, Islam (Frontiers in Plant Science, 2022)
Muscadine berries display enhanced nutraceutical value due to the accumulation of distinctive phytochemical constituents with great potential antioxidant activity. Such nutritional and health merits are not only restricted to muscadine, but muscadine berries accumulate higher amounts of bioactive polyphenolics compared with other grape species. For the genetic study of the antioxidant trait in muscadine, a multi-locus genome-wide association study (GWAS) with 350 muscadine genotypes and 1283 RNase H2 enzyme-dependent amplicon sequencing (rhAmpSeq) markers was performed. Phenotyping was conducted with several antioxidant-related traits, including total phenolic content (TPC), total flavonoid content (TFC), DPPH free radical scavenging activity, and FRAP antioxidant assay in muscadine berry skin. The correlation coefficient analysis revealed that the TPC, and DPPH/FRAP activities were significantly correlated. Through the GWAS analysis, 12 QTNs were identified from the four traits, of which six were pleiotropic QTNs. Two pleiotropic QTNs, chr2_14464718 and chr4_16491374, were commonly identified from the TPC and DPPH/FRAP activities. Co-located genes with the two pleiotropic QTNs were isolated, and two candidate genes were identified with transcriptome analysis. UDP-glycosyltransferase and 4-hydroxy-4-methyl-2-oxoglutarate aldolase were the candidate genes that are positively and negatively correlated to the quantitative property of traits, respectively. These results are the first genetic evidence of the quantitative property of antioxidants in muscadine and provide genetic resources for breeding antioxidant-rich cultivars for both Muscadinia and Euvitis species.